In situ synthesis and preconcentration of cetylpyridinium complexed hexaiodo platinum nanoparticles from spent automobile catalytic converter leachate using cloud point extraction - Aruna Jyothi Kora; K. Madhavi; N.N. Meeravali; Sunil Jai Kumar (Arabian Journal of Chemistry, 2020)
In the present study, a green chemistry based cloud point extraction (CPE) method has been developed for the in situ synthesis and preconcentration of cetylpyridinium complexed hexaiodo platinum nanoparticles (Pt-I NP) from the leachate of spent automobile catalytic converter using potassium iodide (KI) and assisted by a combination of cationic and non-ionic surfactants; cetylpyridinium bromide (CPB) and Triton X-114, respectively. The process parameters such as concentrations of hydrochloric acid, platinum, KI, sodium chloride, CPB, Triton X-114; incubation temperature and complexation time on CPE were optimized. The synthesized nanoparticles were characterized by UV–visible spectroscopy (UV–vis), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and zeta potential techniques. The formation of Pt-I NP was followed with UV–vis. The XRD pattern established the tetragonal crystal structure of the produced nanoparticles. The nanoparticles were spherical in shape and the particle size obtained with TEM was about 5.6 nm. Further, the preconcentrated nanoparticles were quantified by continuum source electro-thermal atomic absorption spectrometry (ET-AAS) and a preconcentration factor of 25 was obtained for a reaction volume of 25 mL. The accuracy of the developed method was confirmed by analyzing the certified reference materials such as CCRMP PTM-1a (copper-nickel sulphide matte) and CCRMP PTC-1a (copper-nickel sulphide concentrate). The current CPE protocol demonstrates advantages such as simultaneous synthesis and preconcentration; synthesis at micromolar concentration from metal scrap, higher nanoparticle recovery; biodegradability and biocompatibility of the employed surfactants and dual solubility of the synthesized Pt-I NP. Thus, the developed method can be applied for the separation, large scale synthesis and preconcentration of Pt-I NP from various environmental and industrial wastes, in a single pot. Keywords: Cetylpyridinium complexed hexaiodo platinum nanoparticles (Pt-I NP), Catalytic converter, Characterization, Cloud point extraction, ET-AAS, Solubility